Face to Face and Side by Side: Printing Cross-Confessional Poetry in Late xvith and Early xviith century France - Barker, S. (Mémoires du livre / Studies in Book Culture, 2013)
The early modern anthology allowed editors to assemble new products quickly without waiting for fresh work to be written, something which proved to be particularly fruitful for poetry collections. However, it is often hard to discern how such collections were developed and assembled. The popular Cantiques du Sieur de Maisonfleur appeared in eight variations between 1580 and 1613. What makes this particular collection all the more intriguing is the cross-confessional background of the poets involved, especially as the collected works had a spiritual focus. This study explores both the changing editorial aims and textual presentation of the Cantiques. It considers the evolving layout and ordering of the works and the different reading apparatus introduced into the volumes so as to discern how readers were meant to approach the collection. It argues that the editorial decisions behind this collection reflected the cross-confessional trends of the later Reformation, particularly how they manifested themselves in a France dealing with the realities and legacies of religious civil war.